Contributors to nonsuicidal self-injury in incarcerated youth - Larkin Street McReynolds; Gail Wasserman; Elise Ozbardakci (BMC, 2017)
Abstract Background Despite elevations in risks associated with self-injurious behavior among community adolescents, the degree to which these features are associated with self-injury among incarcerated youth has rarely been examined. Although the DSM-5 recently proposed a distinct category of nonsuicidal self-injury (NSSI), most studies of youths in forensic settings have not distinguished between subtypes of self-harming individuals. Methods Demographic, offense, and disorder contributors to NSSI in incarcerated youths of both genders (N = 358) were examined via a computerized self-report instrument (VISA), largely consistent with DSM-5. Results Nonsuicidal self-injurers (vs. non-injurers) were almost three times as likely to be white, slightly younger, and more than seven times as likely to have also made a suicide attempt. While males and females reported different rates of exposure to different types of assaultive violence, both nonsexual assault and forced sexual activity were approximately twice as likely among those reporting NSSI in both genders. Conclusion Finding support standardized, universal screening for nonsuicidal self-injury in juvenile justice secure care facilities.